THE DETERMINANTS OF MARKET VALUE OF SYARIAH STOCKS IN JAKARTA ISLAMIC INDEX (JII) - Raisya Nada Salsabila; Muhammad Nafik Hadi Ryandono (Universitas Airlangga, 2020)
The goals of this scientific report are to understand determinants of stocks’ market value on Jakarta Islamic Index (JII). Determinants used in this study including cash flow statements, financial ratios, and firm size. This study used quantitative approach which is explanatory research with data panel regression method. Data used in this study is secondary data, which collected from firms annual reports during scientific periods. Populations in this study are Jakarta Islamic Index 30 (JII 30) emitents on 2014-2018 and samples are 15 firms chosen through purposive sampling methods. The results from this study are, cash flow from operating activities, cash flow from investing activities, cash flow from financing activities, profitability ratio, leverage ratio, liquidity ratio, and firm size have a significant effect on firm value (prob. 0.0000), simultanously. Partially, cash flow from operating activities, cash flow from financing activities, liquidity ratio, and firm size has a negative significant effect on firm value, while cash flow from investing activities, profitability ratio, and leverage ratio has a positive significant effect on firm value. Keywords: Price-to-Book Value (PBV), Cash flow statements, Financial ratios, Firm Size, Jakarta Islamic Index (JII)